PENGARUH KITOSAN TERHADAP SITOLOGI GINJAL TIKUS PUTIH (Rattus sp.) JANTAN YANG DIPAPARI PLUMBUM ASETAT - Simatupang, Ulina Catarina Jenni (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2017)
The study aimed to determine the effect of chitosan on the kidney of rats (Rattus sp.) exposed to lead acetate. Thirty five male animals weighing 250g were divided into 7 groups: K group as a control (without treatment), P1 received Pb (40 mg/kg bw as lead acetate), while P2, P3, and P4, all received Pb (40 mg/kg bw) and chitosan (0,5%, 0,75%, and 1% respectively). P5 group received only chitosan (1%) and P6 group received acetic acid. After 7 weeks of treatment, the animals were sacrificed and the kidneys were isolated. Kidney damage was observed with microscopis. Result showed, treatment of Pb (40 mg/kg bw) in male rats caused demage microscopis. Chitosan able to decrease kidney damage resulted from Pb treatment. In conclusion, chotosan has the ability to reduce residue of Pb as well as microstructure damage of rat kidney exposed to Pb.